New winter hardy winter bread wheat cultivar (Triticum aestivum L.) Voloshkova - Л. М. Голик (Plant Varieties Studying and Protection)
Creation of Initial raw for breeding of winter wheat by change of the development type under low temperatures influence was described. Seeds of spring wheat were vernalized in aluminum weighting bottle. By using low temperatures at sawing of M2-6 at the begin ind of optimal terms of sawing of winter wheat, new winter-hardy variety of Voloshkova was bred.